Arbuscular Mycorrhizal Fungi Alleviate the Negative Effects of Iron Oxide Nanoparticles on Bacterial Community in Rhizospheric Soils - Cao, Jiling; Feng, Youzhi; Lin, Xiangui; Wang, Junhua (Frontiers in Environmental Science, 2016)
As a crucial reciprocal partner, arbuscular mycorrhizal fungi (AMF) can alleviate the negative effects of a variety of pollutants on their hosts and soil microbes. In our previous studies, such characteristics of AMF on plant growth were documented in response to metal engineered nanoparticle (ENP) treatments. However, the role of AMF in influencing ENP effects on soil microbes is still under debate. To address this, we investigated the responses of soil microorganisms to iron oxide nanoparticles (FeONPs) along a concentration gradient (0.1, 1.0 and 10.0 mg kg-1) in maize plants inoculated with or without AMF. The results showed that a high concentration of FeONPs significantly decreased the soil bacterial abundance and shifted the community composition, and these negative responses were associated with decreased DOC contents. However, in the presence of AMF, no significant changes in soil biota and DOC contents were observed under FeONPs treatment. These results indicate that AMF alter the effects of FeONPs on soil microorganisms, possibly by influencing plant growth and organic matter released from plant roots, as DOC contents were impacted by AMF. Our findings suggest that AMF can influence FeONP-plant-microbe interactions; therefore, more attention should be focused on plant-associated microbes when evaluating the biological effects of nanoparticles.